2013
DOI: 10.1080/21507716.2013.807892
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Severity of Wrongdoing in Health Care Delivery and Research: Lessons Learned From a Historiometric Study of 100 Cases

Abstract: Background Wrongdoing among physicians and researchers causes myriad problems for patients and research participants. While many articles have been published on professional wrongdoing, our literature review found no studies that examined the rich contextual details of large sets of historical cases of wrongdoing. Methods We examined 100 cases of wrongdoing in healthcare delivery and research using historiometric methods, which involve the statistical description and analysis of coded historical narratives. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…We decided to sample 40 cases of each kind of wrongdoing to create samples of equal size that, based on effect sizes observed in our past studies (DuBois et al, 2013b), would be large enough to detect significant differences if such differences existed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We decided to sample 40 cases of each kind of wrongdoing to create samples of equal size that, based on effect sizes observed in our past studies (DuBois et al, 2013b), would be large enough to detect significant differences if such differences existed.…”
Section: Methodsmentioning
confidence: 99%
“…Continuous variables (such age, date, number of sources consulted) were entered as such; bivariate variables (such as foreign-trained or evidence of insanity plea) were entered as yes/no; and scaled items were scored on a scale from 1 to 3 using a benchmark scoring guide described in DuBois et al (2013b). The meaning of the scale was defined for each variable, e.g., “1 = no evidence of conflicting roles; 2 = conflicting roles were played but managed; and 3 = conflicting roles were played and not managed.” The guide provides examples of each score for each variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is little consensus about the exact processes by which these ethical guidelines must be operationalized. 1 Taking the Hippocratic Oath by new medical graduates as a manifesto of their lifelong commitment to the associated ethical principles of the medical profession is widespread among medical educational institutions, 2,3 but there is plethora of research Correspondence: Abdolreza Shaghaghi Medical Education Research Center, Tabriz University of Medical Sciences, Tabriz 51665-417, Iran Email shaghaghir@tbzmed.ac.ir evidence [4][5][6][7][8][9] to suggest recurrent pattern of deviance from these principles in healthcare delivery or medical education settings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, prior research by the team indicated that these forms of wrongdoing were sufficiently frequent to accrue at least 75 cases in each area of wrongdoing, which was necessary for purposes of statistical modeling. 16…”
Section: Introductionmentioning
confidence: 99%